The influence of cryopreservation and quick-freezing on the mechanical properties of tendons. (7th November 2017) - Oswald, Irina; Rickert, Markus; Brüggemann, Gert-Peter; Niehoff, Anja; Fonseca Ulloa, Carlos Alfonso; Jahnke, Alexander
Abstract: In order to maintain their native properties, cryopreserved tendons are usually used in biomechanical research and in transplantation of allogenic tendon grafts. The use of different study protocols leads to controversy in literature and thus complicates the evaluation of the current literature. The aim of this study consisted in examining the influence of different freezing and thawing temperatures on the mechanical properties of tendons. 60 porcine tendons were frozen at either −80 °C or −20 °C for 7 days and thawed at room or body temperature for 240 or 30 min, respectively. A subgroup of ten tendons was quick-frozen with liquid nitrogen (−196 °C) for 2 s before cryopreservation. Biomechanical testing was performed with a material testing machine and included creep, cyclic and load-to-failure tests. The results showed that freezing leads to a reduced creep strain after constant loading and to an increased secant modulus. Freezing temperature of −80 °C increased the secant modulus and decreased the strain at maximum stress, whereas thawing at room temperature reduced the maximum stress, the strain at initial tendon failure and the Young's Modulus. Quick-freezing led to increased creep strain after constant loading, increased strain at initial failure in the load-to-failure test, and decreased strain at maximum stress. When cryopreserving, tendons for scientific or medical reasons, freezing temperature of −20 °C and thawing temperature of 37.5 °C are recommended to maintain the native properties of tendons. A treatment with liquid nitrogen in the sterilization process of tendon allografts is inadvisable because it alters the tendon properties negatively.